Enhancement of the lower critical field in FeSe-coated Nb structures for superconducting radio-frequency applications. (13th November 2020) - Lin, Zefeng; Qin, Mingyang; Li, Dong; Shen, Peipei; Zhang, Liping; Feng, Zhongpei; Sha, Peng; Miao, Jun; Yuan, Jie; Dong, Xiaoli; Dong, Chao; Qin, Qing; et al.
Abstract: Bulk Nb superconducting radio-frequency (SRF) cavities are widely used in accelerators, and their accelerating gradient and general performance are limited by the superheating field ( B sh ). To push the theoretical limit of the B sh, new multilayer structures are required. We fabricated FeSe-coated Nb films using pulsed laser deposition, performed structural characterizations, and measured the transport and magnetic properties for this superconductor-superconductor bilayer structure with smooth surface. Additionally, the measured B c1 of FeSe-coated Nb film is greatly enhanced, while the B sh of the FeSe layer is expected to be higher than that of bulk Nb, yet the superconducting transition temperature ( T c ) is less than 5 K. This work presents the first fabrication of a new coating layer: FeSe deposited on Nb, showing the possibility of using iron-based materials for multilayer structures in SRF cavities.